Introduction to the quantum world of atoms and molecules - Dahl, Jens Peder (Singapore, New Jersey : World Scientific, 2009)
The rise of atomic theory -- The birth of quantum mechanics -- Wave mechanics -- Particle in a box -- Quantum-mechanical operators -- The free particle -- The harmonic oscillator -- The central field problem -- The hydrogen atom -- The spinning electron -- The periodic table by electron counting -- The variational method -- Diatomic molecules -- Vibration and rotation of diatomic molecules -- Atomic term symbols -- Atomic terms. Wavefunctions and energies -- Electronic terms of diatomic molecules -- The hartree-fock method -- Density-functional theory.
Incluye referencias bibliográficas (p. 446-449) e índice
Keywords: Teoría cuántica; Átomos; Moléculas